MOTIVASI PENINGKATAN KEMAMPUAN PENGGUNAAN KOMPUTER MAHASISWA SEKOLAH TINGGI PENYULUHAN PERTANIAN (MOTIVATION FOR ENHANCEMENT OF COMPUTER USING CAPACITY OF AGRICULTURE EXTENSION COLLEGE) - Sulastiyah, Amie (Jurnal Ilmu-Ilmu Pertanian, 2012)
Sekolah Tinggi Penyuluhan Pertanian (STPP) majoring in agricultural counseling Yogyakarta who has target agricultural counselor civil servants, has a lot of problem to face any ability competition. In that condition we need information which has basis technology (computer). Based on the begining identification result of students in a year we got the computer ability include Microsoft Word, Excel, Power Point and internet the result shows 49.84%. In ability can improve by motivation. The purpose is to understand whether motivation can increase ability in term of computer operational. The benefit of motivation can be used as the study activity for developing capabilities. Motivation in cycle between actions and goals. Hypothesis: Internal and external motivation are factor which can increase the student capabilities. This research was held in (STPP) during a year based on the student activity study from September 2011 - August 2012. Respondents are all the students (30 students) with sensus method. The result from ability for using the computer increasing 20.99 % . It is showed that internal factor which can improve the ability 63.85 % ; internal factor which do not give the improvemnet yet 31 %; external factor which can improved 45 %; and external factor which do not give the improvement yet is 46 %. Increasing an decreasing of motivation can cause by the ability of developing the potential from inside and outside. The conclusion: motivation in a year increasing around 20.99 %.